Pectins, Endopolygalacturonases, and Bioenergy - Latarullo, Mariana B. G.; Tavares, Eveline Q. P.; Padilla, Gabriel; Leite, Débora C. C.; Buckeridge, Marcos S. (Frontiers in Plant Science, 2016)
The precise disassembly of the extracellular matrix of some plant species used as feedstocks for bioenergy production continues to be a major barrier to reach reasonable cost effective bioethanol production. One solution has been the use of pretreatments, which can be effective, but increase even more the cost of processing and also lead to loss of cell wall materials that could otherwise be used in industry. Although pectins are known to account for a relatively low proportion of walls of grasses, their role in recalcitrance to hydrolysis has been shown to be important. In this mini-review, we examine the importance of pectins for cell wall hydrolysis highlighting the work associated with bioenergy. Here we focus on the importance of endopolygalacturonases (EPGs) discovered to date. The EPGs catalogued by CAZy were screened, revealing that most sequences, as well as the scarce structural work performed with EPGs, are from fungi (mostly Aspergillus niger). The comparisons among the EPG from different microorganisms, suggests that EPGs from bacteria and grasses display higher similarity than each of them with fungi. This compilation strongly suggests that structural and functional studies of EPGs, mainly from plants and bacteria, should be a priority of research regarding the use of pectinases for bioenergy production purposes.